2023
DOI: 10.1101/2023.10.18.562677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resting state changes in aging and Parkinson’s disease are shaped by underlying neurotransmission – a normative modeling study

Jan Kasper,
Svenja Caspers,
Leon D. Lotter
et al.

Abstract: Human healthy and pathological aging is linked to a steady decline in brain resting state activity and connectivity measures. The neurophysiological mechanisms underlying these changes remain poorly understood. Making use of recent developments in normative modeling and availability of in vivo maps for various neurochemical systems, we test in the UK Biobank cohort (N=25,917) if and how age- and Parkinson's disease related resting state changes in commonly applied local and global activity and connectivity mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…The spatial colocalization framework constitutes a powerful and flexible tool to study biological underpinnings of both typical and atypical human brain processes in vivo . While its application in a wide range of neuroimaging contexts has brought valuable insights into the neurobiology of structural 76,32,31 and functional 77 brain development, as well as brain organization in health 25 and disease 26,40,41 , inferences from spatial colocalization analyses are usually limited to an associative, non-causal level. Notably, this also is the case for our present study, in which all reported associations can only provide indirect evidence for involvement of specific neurobiological markers in cortical development and aging, not providing actual mechanistic explanations.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial colocalization framework constitutes a powerful and flexible tool to study biological underpinnings of both typical and atypical human brain processes in vivo . While its application in a wide range of neuroimaging contexts has brought valuable insights into the neurobiology of structural 76,32,31 and functional 77 brain development, as well as brain organization in health 25 and disease 26,40,41 , inferences from spatial colocalization analyses are usually limited to an associative, non-causal level. Notably, this also is the case for our present study, in which all reported associations can only provide indirect evidence for involvement of specific neurobiological markers in cortical development and aging, not providing actual mechanistic explanations.…”
Section: Discussionmentioning
confidence: 99%